1992
DOI: 10.3892/ijo_00000031
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone I effectively induces apoptosis in estrogen receptor-positive (MCF-7) and estrogen receptor-negative (MDA-MB-231) breast cancer cells

Abstract: Abstract. Danshen (Salvia miltiorrhiza Bunge) is a herb that has been widely and successfully used for treating inflammatory diseases in clinics in Asia. The relatively abundant tanshinones, tanshinone I, tanshinone IIA, cryptotanshinone, and dihydrotanshinone, have been isolated from Danshen. These tanshinones are the major diterpenes isolated from Danshen, and show cytotoxic effects on cell lines derived from human carcinomas of the colon, ovary, lung, mouth, and breast. Recently, anti-cancer activities of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
79
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(88 citation statements)
references
References 7 publications
5
79
1
Order By: Relevance
“…[48] Given that CYP2E1 gene expression is under the transcriptional control of factors responsive to inflammation [19,29,49,50] it was theorized that inhibition of glycolysis in breast cancer cells bearing diverse genetic background would lead to alternative CYP2E1 cellular levels and hence dissimilar ROS. [42] On the other side inhibition of glycolysis would lead to increased ROS generation [31] that could be altered by CYP2E1 enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…[48] Given that CYP2E1 gene expression is under the transcriptional control of factors responsive to inflammation [19,29,49,50] it was theorized that inhibition of glycolysis in breast cancer cells bearing diverse genetic background would lead to alternative CYP2E1 cellular levels and hence dissimilar ROS. [42] On the other side inhibition of glycolysis would lead to increased ROS generation [31] that could be altered by CYP2E1 enzymatic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the levels of ER and drug sensitivity status, breast cancers falls into two broad categories, ER-positive or ER-negative types (18). ER is expressed in about 60% of all breast cancers, which generally possess better prognosis and is often responsive to anti-estrogen therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Curiously, several reports still claim the presence of caspase-3 in the breast carcinoma cell line MCF-7 in which this enzyme is supposed to contribute to apoptosis signaling [7][8][9][10][11][12][13][14][15]. This was not only demonstrated indirectly via fluorometric assay systems measuring caspase-3-like activities-that might be also elicited by the closely related caspase-7-but by Western blotting analyses demonstrating directly the presence of this protease in MCF-7 cells.…”
mentioning
confidence: 99%
“…In addition, it was shown that caspase-3 is the primary activator of apoptotic (low molecular) DNA fragmentation via cleavage-mediated inhibition of ICAD [22]. Thus, it is puzzling that caspase-3-deficient MCF-7 cells exhibit DNA fragmentation and other apoptotic characteristics following cell death induction as described [7][8][9][10][11][12][13][14][15]. While it is still possible that caspase-3-deficient MCF-7 cells display high molecular weight DNA fragmentation that might be occasionally mistaken for the typical apoptotic DNA fragmentation, the detection of a caspase-3 protein in MCF-7 cells [7,8,11,[13][14][15] with a partially deleted CASP-3 gene is cause for concern.…”
mentioning
confidence: 99%